Drug Disposal and Ecopharmacovigilance Practices in the Krowor Municipality, Ghana - Yvonne Yirenkyiwaa Esseku; Priscilla Kolibea Mante; Alex Nii Oto Dodoo; Eric Woode (Journal of Toxicology)
Introduction. The use of medicines is a ubiquitous practice for the management of healthcare conditions. In the delivery of healthcare, medicines may remain unused and may expire within the various stakeholders in the pharmaceutical value chain. If these unused and expired medicines are not disposed of properly, they may result in the concentration of pharmaceuticals in environmental media contaminating food sources for humans and animals. Implementation of ecopharmacovigilance strategies will reduce the quantities of pharmaceuticals in the environmental media, reduce the potential for inadvertent consumption by humans and animals, and reduce potential pharmacological effects on the environment, humans, and animals. The drug disposal flow diagram (DDFD) provides an effective way of assessing the most cost-effective strategies to reduce environmental contamination. Method. A combined method of desk study and questionnaires, both structured and unstructured was used. The desk study reviewed the institutional arrangements for the regulation of disposal of pharmaceutical waste in Krowor. The questionnaires were used to gather information from community members, community pharmacies, and pharmaceutical manufacturers in Krowor. Results. The drug disposal flow diagram shows that up to 96% of pharmaceuticals are handled and disposed of in ways that are harmful to the environment with only 4% being handled in ways that are environmentally friendly. Forty-nine percent (49%) of generated pharmaceutical waste ends up in the local and surrounding areas, 21% contaminates the drainage system and 25% is discharged into receiving waters. Discussion. The DDFD for Krowor shows that engagement with community members and institutional healthcare service providers and strategies that result in separation of pharmaceutical waste from general household waste will reduce the quantities of pharmaceuticals that end up in the environmental media. Conclusion. The DDFD will support the effective implementation of ecopharmacovigilance (EPV) strategies.